2020
DOI: 10.3389/fendo.2020.00145
|View full text |Cite
|
Sign up to set email alerts
|

Role of Brown Adipose Tissue in Adiposity Associated With Narcolepsy Type 1

Abstract: Narcolepsy type 1 is a neurological sleep-wake disorder caused by the destruction of orexin (hypocretin)-producing neurons. These neurons are particularly located in the lateral hypothalamus and have widespread projections throughout the brain, where they are involved, e.g., in the regulation of the sleep-wake cycle and appetite. Interestingly, a higher prevalence of obesity has been reported in patients with narcolepsy type 1 compared to healthy controls, despite a normal to decreased food intake and comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 121 publications
(170 reference statements)
0
11
0
Order By: Relevance
“…To support the role of orexins in obesity resistance, several animal studies have demonstrated that OrxA injections into several cerebral areas, such as the rostral LH, paraventricular nucleus, TMN, LC, DRN, nucleus accumbens, and substantia nigra, improve SPA and NEAT [ 132 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ], while repeated injections of OrxA into LH are associated with reduced fat mass [ 153 ]. Orexins also exert a sympathoexcitatory effect, as demonstrated by increased blood pressure and heart rate, increased sympathetic outflow to brown adipose tissue (BAT), and increased plasma epinephrine and noradrenaline release [ 141 , 154 , 155 , 156 ]. The sympathetic outflow to BAT may be a cause of the increase in NEAT due to orexin [ 157 ].…”
Section: Feeding Behavior Energy Homeostasis and Obesitymentioning
confidence: 99%
“…To support the role of orexins in obesity resistance, several animal studies have demonstrated that OrxA injections into several cerebral areas, such as the rostral LH, paraventricular nucleus, TMN, LC, DRN, nucleus accumbens, and substantia nigra, improve SPA and NEAT [ 132 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ], while repeated injections of OrxA into LH are associated with reduced fat mass [ 153 ]. Orexins also exert a sympathoexcitatory effect, as demonstrated by increased blood pressure and heart rate, increased sympathetic outflow to brown adipose tissue (BAT), and increased plasma epinephrine and noradrenaline release [ 141 , 154 , 155 , 156 ]. The sympathetic outflow to BAT may be a cause of the increase in NEAT due to orexin [ 157 ].…”
Section: Feeding Behavior Energy Homeostasis and Obesitymentioning
confidence: 99%
“…In addition, orexin is largely sympathoexcitatory (Teske & Mavanji, 2012 ). Studies in rodents demonstrate that orexin enhanced sympathetic outflow as indicated by elevated blood pressure and heart rate (Teske & Mavanji, 2012 ), increased renal sympathetic nerve activity including to the brown adipose tissue (BAT) (Straat et al, 2020 ), and elevated plasma epinephrine, noradrenaline release, and firing rate of sympathetic nerves (Teske & Mavanji, 2012 ). This indicates that orexin‐induced NEAT has “extra” caloric expenditure which may be via sympathetic output to BAT (Morrison et al, 2014 ).…”
Section: Orexinsmentioning
confidence: 99%
“…Patients with narcolepsy often gain weight, and the body mass index (BMI) of adults in this group is approximately 15% higher than the average BMI [ 4 ]. This has been attributed to orexin-mediated food-seeking behavior [ 70 ], a lower metabolic rate in orexin-deficient individuals [ 71 ], and the effect of the orexin system on brown adipose tissue functionality, which could be partly responsible for the impaired energy homeostasis, potentially resulting in increased adiposity and weight gain in patients with NT1 [ 71 ]. Compared with individuals without narcolepsy, patients with narcolepsy have a higher prevalence of diabetes (by 9.3%) and obesity (by 8.8%) [ 22 ].…”
Section: Confounding Factors In the Diagnosis Of Narcolepsymentioning
confidence: 99%